2022
DOI: 10.1155/2022/7977937
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTM1 and GSTT1 Null Genotypes with Toluene Diisocyanate-Induced Asthma

Abstract: Background. Toluene diisocyanate (TDI) causes occupational asthma by generating oxidative stress, leading to tissue injury and inflammation. Glutathione transferases (GSTs) are detoxifying enzymes that eliminate oxidative stress. We examined whether the genotypes of the GSTM1 and GSTT1 genes are associated with TDI-induced occupational asthma (TDI-OA). Methods. The study population consisted of 26 asthmatics with a positive response to the TDI challenge (TDI-PA) and 27 asthmatics with negative responses (TDI-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In our study, we found higher prevalence of the GSTM1 null variant and at least one null variant of either GSTM1 or GSTT1 in COPD patients. Based on the experimental studies of Seidegård et al [ 33 ], as well as the results of Lee et al [ 34 ], concerning the effects of the null variant of GSTM1 and GSTT1 genes on enzyme activity and enzyme protein levels, we suggest that the loss of enzymatic activity in COPD patients that carry the null GSTM1 variant results in altered antioxidant defense and the detoxification of ROS and their products. This additionally contributes to the pathological changes present in COPD due to oxidation and inflammation…”
Section: Discussionmentioning
confidence: 69%
“…In our study, we found higher prevalence of the GSTM1 null variant and at least one null variant of either GSTM1 or GSTT1 in COPD patients. Based on the experimental studies of Seidegård et al [ 33 ], as well as the results of Lee et al [ 34 ], concerning the effects of the null variant of GSTM1 and GSTT1 genes on enzyme activity and enzyme protein levels, we suggest that the loss of enzymatic activity in COPD patients that carry the null GSTM1 variant results in altered antioxidant defense and the detoxification of ROS and their products. This additionally contributes to the pathological changes present in COPD due to oxidation and inflammation…”
Section: Discussionmentioning
confidence: 69%
“…The null polymorphism, which arises in GSTM1due to the complete gene deletion and lack of GST function, has been connected to the development and onset of various illnesses such as psoriasis, atherosclerotic cardiovascular disease (ASCVD), malignancy and type 2 diabetes mellitus (DM2) (Lee et al, 2022; Sobha and Ebenezar 2022). The null genotype polymorphism causes oxidative stress due to the decreased antioxidant capacity, which results in inflammation and other cellular dysfunctions in chronic disorders (Lee et al, 2022). The genotype GSTM1 null is linked to a higher risk of cardiovascular disease (Bhatti et al, 2018).…”
Section: Resultsmentioning
confidence: 99%